Memengaruhi self identity, social influence untuk decisions to visit objek wisata hutan bakau: Tinjauan pustaka - Andre Ludya Liap; Dudi Permana; Adi Nurmahdi; Mas Wahyu Wibowo; Ding Chong (Jurnal Doktor Manajemen (JDM), 2023)
This study conducted a literature review of existing research in Indonesia on tourist visits to mangrove forests as eco-tourism. Based on the 20 (twenty) studies that the author has reviewed, there are 19 (nineteen) previous studies that have studied the supply side far more. The feasibility of developing mangrove eco-tourism based on the supply side, namely; tourist attraction objects, accessibility to objects, socio-economic conditions of the community, modes of transportation and accommodation, supervision management, supporting facilities and infrastructure, availability of clean water within the object area, relations between tourists and people around the area, value of carrying capacity, and security of the area . There is still a little research from the demand side that researchers do through the google scholar search system and sort from the top to the bottom of the 20 selected journals. Only one study uses the theoretical basis of Ajzen and Fishbein (1980) as a theoretical model of responsible environmental behavior or a model of their responsible environmental behavior based on the theory of planned behavior (TPB) (Ajzen, 2020). Researchers on the demand side or requests from visitors' desires are still lacking in research that should be encouraged to be able to increase self identity or social influence making environmental consciousness, pro-environmental behavior, and environmental belief a mediating or moderating variable so as to produce a significant or positive analysis on behavior for the decision to visit the mangrove forest eco-tourism is more sustainable.